Constitutional history of the American Revolution. Vol. 4, The authority of law - Reid, John Phillip (Madison, Wis. : University of Wisconsin Press, 1993)
Annotation "This is the first comprehensive study of the constitutionality of the Parliamentary legislation cited by the American Continental Congress as a justification for its rebellion against Great Britain in 1776. The content and purpose of that legislation is well known to historians, but here John Phillip Reid places it in the context of eighteenth-century constitutional doctrine and discusses its legality in terms of the intellectual premises of eighteenth-century Anglo-American legal values." "The Authority of Law is the last of a four-volume work, preceded by The Authority to Tax, The Authority of Rights, and The Authority to Legislate. In these previous volumes, Reid argued that there would have been no rebellion had taxation been the only constitutional topic of controversy, that issues of rights actually played a larger role in the drafting of state and federal constitutions than they did in instigating a rebellion, and that the American colonists finally took to the battlefield against the British because of statutes that forced Americans to either concede the authority to legislate or leave the empire." "Expanding on the evidence presented in the first three volumes, The Authority of Law determines the constitutional issues dividing American whigs from British imperialists. Reid summarizes these issues as "the supremacy issue," "the Glorious Revolution issue," "the liberty issue," and the "representation issue." He then raises a compelling question: why, with so many outstanding lawyers participating in the debate, did no one devise a constitutionally legal way out of the standoff? Reid makes an original suggestion. No constitutional solution was found because the British were more threatened by American legal theory than the Americans were by British theory. British lawyers saw the future of liberty in Great Britain endangered by the American version of constitutional law." "Considered as a whole, Reid's Constitutional History of the American Revolution contributes to an understanding of the central role of legal and constitutional standards, especially concern for rule by law, in the development of the American nation."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Constitutional history -- United States; United States -- Politics and government -- 1775-1783.; Histoire constitutionnelle -- États-Unis.; États-Unis -- Politique et gouvernement -- 1775-1783.; LAW -- Constitutional; LAW -- Public; Constitutional history; Politics and government; United States; Staatsrecht; Verenigde Staten; 1775 - 1783